2003
DOI: 10.1016/s0042-6822(03)00507-5
|View full text |Cite
|
Sign up to set email alerts
|

Human rotavirus specific T cells: quantification by ELISPOT and expression of homing receptors on CD4+ T cells

Abstract: Using an intracellular cytokine assay, we recently showed that the frequencies of rotavirus (RV)-specific CD4(+) and CD8(+) T cells secreting INFgamma, circulating in RV infected and healthy adults, are very low compared to the frequencies of circulating cytomegalovirus (CMV) reactive T cells in comparable individuals. In children with acute RV infection, these T cells were barely or not detectable. In the present study, an ELISPOT assay enabled detection of circulating RV-specific INFgamma-secreting cells in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
36
0
13

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 30 publications
5
36
0
13
Order By: Relevance
“…between IFN-γ producing T cell frequencies in blood at challenge and clinical signs post-challenge in the same pigs). Recent studies of T cell responses in human PBL showed that in rotavirus infected children, virus-specific CD4+ and CD8+ T cells that secreted IFN-γ were very low or undetectable [19,49]. Similar results were found in studies of rotavirus-infected juvenile rhesus macaques monkeys [50].…”
Section: Discussionsupporting
confidence: 62%
“…between IFN-γ producing T cell frequencies in blood at challenge and clinical signs post-challenge in the same pigs). Recent studies of T cell responses in human PBL showed that in rotavirus infected children, virus-specific CD4+ and CD8+ T cells that secreted IFN-γ were very low or undetectable [19,49]. Similar results were found in studies of rotavirus-infected juvenile rhesus macaques monkeys [50].…”
Section: Discussionsupporting
confidence: 62%
“…The oral mode of delivery has the potential to confer long-term mucosal immunity against pathogens such as HIV-1 if it can induce antigen specific cells to home to the gut as shown in previous studies [25][26][27][28], but efforts to stimulate immunity through this route may inadvertently induce oral tolerance instead [29]. Oral vaccine development using replication defective adenovirus, such as the vector we have tested, may be impeded by vector instability in the acidic environment of the stomach, through which it must pass to ensure antigen presentation and maximum exposure to and uptake by the antigen presenting cells of the intestine.…”
Section: Discussionmentioning
confidence: 99%
“…3 Similar to RV-mBc, in healthy adults RV-T cells express intestinal migration markers, suggesting that they may be reflecting intestinal RV-T cells. 89 Most children with natural infection have undetectable or very low levels of RV-T cells measured by their capacity to secrete interferon gamma upon stimulation with antigen in vitro. 90 Recent development of class II cell tetramers with RVspecific epitopes allowed detection of circulating RV-CD4 T cells that express intestinal homing receptors in healthy adults, and in children vaccinated with RIX4414.…”
Section: Rv-specific T Cellsmentioning
confidence: 99%